ROOT CAUSE ANALYSIS DARI INKONSISTENSI PEMELIHARAAN PERALATAN MEDIS DI RUMAH SAKIT “X” - Arifin, M Syamsul (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Root Cause Analysis of Inconsistencies in Medical Equipment Maintenance at Hospital 'X'. The purpose of this study is to identify the variables responsible for the lack of consistency in the maintenance of medical equipment at